2016
DOI: 10.1016/j.ijscr.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Ewing sarcoma/primitive neuroectodermal tumor of the kidney

Abstract: HighlightsEwing sarcoma/primitive neuroectodermal tumor of the kidney (ES/PNET) is a member of Ewing’s sarcoma family, occurring in young adults.The clinical course and prognosis of ES/PNET are different from renal cell carcinoma (RCC).For definite diagnosis, in addition to cytogenetic analysis; other techniques may be needed; such as fluorescent in situ hybridization (FISH), reverse transcriptase-polymerase chain reaction (RT-PCR) of the t (11; 22) translocation [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…4 Other studies also showed mean age of 27 for the diagnosis of these cases. 1,2,4 In our study, the age of two patients was 25 years and the third one was 35 years.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…4 Other studies also showed mean age of 27 for the diagnosis of these cases. 1,2,4 In our study, the age of two patients was 25 years and the third one was 35 years.…”
Section: Discussionmentioning
confidence: 65%
“…Renal PNET/ESis a member of Ewing sarcoma family. [1][2][3] They are rare tumors originating from the neural crest and are more aggressive than PNET at any other site. 5 Rafael et al in study of 11 cases observed that most common age of diagnosis was between 18 to 45 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both types have characteristics of a high degree of malignancy, a common distant metastasis, and local recurrence. The incidence ratio of male to female is around 3:1 (5,6). PNET tends to recur locally and to metastasize early to regional lymph nodes, lungs, liver, bone, and bone marrow within 2 to 3 years after surgery, with a resulting of very poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This case has been approached and reported according to the SCARE criteria [3] . Presentation of such tumors reported in the literature is non-specific and frequently involves localized pain which usually involves flank, subcostal or abdominal area with or without hematuria [4] , [5] , [6] , [7] . The presence of a vascular thrombus has been reported as a distinctive feature of renal ESFT/PNET [7] , [8] , [9] , [10] , [11] .…”
Section: Discussionmentioning
confidence: 99%